Coordinated surveillance system under the One Health approach for cross‐border pathogens that threaten the Union – options for sustainable surveillance strategies for priority pathogens - European Food Safety Authority (EFSA); John Berezowski; Katinka De Balogh; Fernanda C Dórea; Simon Ruegg; Alessandro Broglia; Gabriele Zancanaro; Andrea Gervelmeyer (EFSA Journal)
Abstract This report provides guidance for Member states who plan to submit applications under the work programme ‘CP‐g‐22‐04.01 Direct grants to Member States' authorities’. The priority pathogens on which the coordinated surveillance under the grant initiative shall focus have been identified in a prioritisation exercise with Member States and ECDC. These are Crimean Congo haemorrhagic fever, echinococcosis, hepatitis E, highly pathogenic avian influenza (HPAI), influenza in swine, Lyme disease, Q‐fever, Rift Valley fever, tick‐borne encephalitis, West Nile fever and Disease X (Disease Y of animals). Surveillance activities (surveillance cards) have been proposed for these agents in this report. Member States should select one or more diseases from the list of priority diseases and then choose surveillance activities from the surveillance cards and modify them where needed, to reflect their national needs and situation. Member States can also design alternative surveillance activities for the priority infectious agents that may better fit the epidemiological situation in their country. Further, this report provides a section on surveillance perspectives that links infectious agents to different hosts, allowing Member States to consider the testing for multiple infectious agents in samples from a single host population, as well as sections providing guidance on surveillance in vectors and wildlife and for Disease X (Disease Y in animals). Member States are encouraged to develop cross‐sectoral collaborations and the report provides guidance on cross‐sectoral collaboration to help them. Finally, there is a roadmap providing an overall description of the steps in the process of developing a surveillance system in order to apply for the grant.